Hospital and healthcare security - York, Tony W.; MacAlister, Don. (Oxford : Butterworth-Heinemann, 2015)
Building on the foundation of the previous five editions, this edition includes new and updated chapters to reflect the current state of healthcare security, particularly in data security and patient privacy, patient-generated violence, and emergency preparedness and management. Conveying a wide spectrum of topics in an easy to comprehend format, it provides a fresh perspective for healthcare security professionals to better prepare for security issues before they occur. Features include: a quick-start section for hospital administrators who need an overview of security issues and best practices; a sample request for proposal (RFP) for healthcare security services and incident report classifications; and general principles clearly laid out so readers can apply internationally recognized industry standards most appropriate to their own environment. --
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Hospitals -- Security measures; Health facilities -- Security measures; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Health facilities -- Security measures; Hospitals -- Security measures; Electronic books; Electronic books